The Role of Bacillus sp. in Reducing Chemical Inputs for Sustainable Crop Production - Luziane Ramos Sales; Everlon Cid Rigobelo (Agronomy)
Bacillus species have emerged as promising agents for reducing chemical input in sustainable crop production. These bacteria possess diverse abilities, including nutrient cycling, phytohormone production, and stress tolerance enhancement in plants. Recent advances in omics technologies have revolutionized the understanding of Bacillus sp. biology and expanded their potential applications. Bacillus-based products have demonstrated effectiveness in reducing nitrogen and phosphorus fertilizer requirements while maintaining or improving crop yields. However, their field performance may be inconsistent, highlighting the need for further research to optimize formulations and delivery methods. The compatibility with other agricultural inputs varies depending on the specific chemicals and conditions involved. The introduction of Bacillus sp. can significantly affect the soil microbiome, potentially promoting plant growth and microbial diversity. Strain specificity and host compatibility play crucial roles in determining the success of host–parasite interactions. The regulatory and safety aspects require further investigation to ensure the safe and sustainable use of Bacillus species in various applications. The integration of Bacillus-based products into existing crop management systems, following the principles of Integrated Pest Management and Integrated Crop Management, is essential for their successful implementation. This review provides a comprehensive overview of the current knowledge on Bacillus sp. for reducing chemical inputs for sustainable crop production, highlighting the challenges and opportunities for future research and application.